Students’ Perception on the Use of Online Assessment in English Summative Tests at MAN Kota Sorong. - Sanaky, Kenaidia Restinela; Rachma, Rachma; Selfiyanti, Selfiyanti; Syahrul, Syahrul; Hasanudin, Hasanudin (JOLIES : Journal of Linguistic and English Studies, 2024)
After passing through the covid-19 pandemic since the end of 2019, the student learning process initially carried out face-to-face must be changed to remote or online. All learning activities must be re-planned according to the context of online learning using technology and internet connections. The implementation of summative assessment in an online learning environment basically is not significantly different from the summative assessment which is carried out face-to-face. One of the most visible differences is the use of media or technology that is supported by internet access. Therefore, in this study the researcher will examine the summative assessment that takes place at the end of the learning process about the students’ perception on the use of online assessment in English summative test. The method of this research is qualitative research based on the interview which is assigned to students in MAN Kota Sorong. Interviews were also conducted to obtain more detailed data related to the purpose of finding out students' perceptions of the use of online assessment in English summative tests. The participants of this research were 9 students from the third grade of language class at MAN Kota Sorong. The results show that students had negative and positive perceptions which relate to the basic principles of assessment. It was divided into three perceptions such as (1) Online Assessment Improve Test Practicality. (2) Online Assessment Decreases Test Practicality. (3) Online Assessment Questionable For Authenticity.